Une éducation à l’olympisme est-elle possible ? - Christophe Maillard; Éric Monnin (Éducation et Socialisation)
The Olympic educational concept, appeared in the 1970s, can answer the concern of the CIO to give itself a positive image by mobilizing the youth behind the eternal flame. Multiple initiatives or programs were developed in the world (China, Greece, Australia, France…). It is so interesting to give to the pupils a critical look of Olympics games resting on this project: to educate, it so is to offer a political and cultural frame renewed with a cultural and pacifist purpose. It would also allow to offer a look distanced on a widely celebrated and mediatized international event, which joins in a trade and social logic. It is in this context that the youth can benefit of a real Olympic education and that the education in the Olympic movement will can benefit from a real Olympic education and that the education in the Olympic movement can take its place within the “various teachings in” recommended by the Department of Education.